Dancers & the dance : stories - Brenner, Summer (Minneapolis : Coffee House Press ; Saint Paul, Minn. : Dist ributed to trade by Consortium Book Sales and Distribution, 1990)
A collection of twelve stories exploring the complex world of dancer s.